A dinitrogen complex without donor ligands: isolation and characterization of a (Mn(CO)5(η1-N2))+ salt - Sellin, Malte; Watson, James D.; Fischer, Julia; Schmitt, Manuel; Ball, Graham E.; Field, Leslie D.; Krossing, Ingo (Journal of the American Chemical Society, 2025)
Dinitrogen complexes are intermediates in nitrogen fixation. Until now, all isolated molecular dinitrogen complexes have relied on ancillary ligands that are net electron donors, yielding N2 ligands carrying a clear negative partial charge. Here, we present the synthesis, isolation, and characterization of the complex salt [Mn(CO)5(η1-N2)]+[F(Al(ORF)3)2]− (RF = C(CF3)3) that resulted from the oxidation of Mn2(CO)10 under a dinitrogen atmosphere in pentafluorobenzene solvent. The IR/Raman spectra reveal a high N2 frequency of 2301/2303 cm-1 close to free N2 gas (2330 cm-1) that indicates little π-back-donation. QTAIM and CD-NOCV analyses show that the carbonyl ligands act as net acceptor ligands that induce the formation of an inversely polarized dinitrogen ligand with a +0.2 charge on the terminal atom that holds the potential to be susceptible to nucleophilic attack.